CASE REPORT: SKIN ABLATION IN METATARSAL SINISTRA OF LOCAL DOG - Tanaya, I Gede Raka Mas; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2022)
In general, ablation means the loss of tissue that is characterized by the presence of wounds. Skin ablation is characterized by dislodging of the skin from the tissue which causes wide open wounds. A local dog 4 months old, 4 kg body weight and male sex were examined at the Educational Animal Hospital, Faculty of Veterinary Medicine, Udayana University with complaints of open wounds due to dislodged skin on the left metatarsal caused by sharp incisions with a diameter of about 3 cm. Handling the skin ablation with surgery with a skin graft technique. The wound healing of skin grafts is determined by animal care, namely by keeping the wound dressing always in dry condition, preventing animals from licking the skin of the donor, and administering anti-inflammatory syrup with amoxsan syrup for 7 days.